Physician perceptions of blood pressure control in patients with chronic kidney disease and target blood pressure achievement rate - Ran-hui Cha; Hajeong Lee; Jung Pyo Lee; Young Rim Song; Sung Gyun Kim; Yon Su Kim (The Korean Society of Nephrology, 2017)
Background: Blood pressure (BP) control is the most-established method for the prevention of chronic kidney disease (CKD) progression. However, the ideal BP target for CKD patients is still under debate. Methods: We performed a survey of regular registered members of the Korean Society of Nephrology to determine physician perceptions of BP control in patients with CKD. In addition, we evaluated the target BP achievement rate using data from the APrODiTe-2 study. Results: Two-thirds of physicians considered the target BP for CKD to be < 130/85 mmHg. The systolic BP (SBP) thresholds for diabetic CKD, proteinuria ≥ 300 mg/day, 30 ≤ glomerular filtration rate (GFR) < 60 mL/min/1.73 m², age < 60 years, and the presence of atherosclerotic (ASO) complications were significantly lower than the SBP thresholds of the opposite parameters. The three major hurdles to controlling BP were non-compliance with lifestyle modification and medications, and self-report of well-controlled home BP. Most physicians prescribed home and ambulatory BP monitoring to less than 50% of their patients. The target BP achievement rates using the SBP thresholds in this survey were as follows: non-diabetic (69.3%); diabetic (29.5%); proteinuria < 300 mg/day (72.3%); proteinuria > 300 mg/day (33.7%); GFR ≥ 60 (76.4%); GFR < 30 (47.8%); no evidence of ASO (67.8%); and the presence of ASO (42.9%). Conclusion: The target BP was lower in patients with higher cerebro-cardiovascular risks. These patient groups also showed lower target BP achievement rates. We also found a relatively lower application and clinical reflection rate of home or ambulatory BP monitoring.